Organization of Islamic Education Curriculum to Prevent Radicalism Among Students in Indonesian Universities - Zainal Arifin; Thifal Khansa Nabila; Sri Rahmi; Atika (Jurnal Pendidikan Agama Islam, 2025)
Purpose – The purpose of this study is to examine strategies for preventing radicalism infiltration among students at state universities by strengthening Compulsory Curriculum Courses Islamic Religious Education learning at Universitas Gajah Mada Yogyakarta and Universitas Syiah Kuala (USK) Aceh. Design/methods/approach – This research is field research with a qualitative approach. Data collection techniques include interviews, observation, open questionnaires, and documentation. Data analysis uses Miles et al theory, which includes three activities: data condensation, data display, and conclusion drawing (verification). Findings – The results of the study show, first, that Islamic Religiuos Education as a compulsory subject in the Universitas Gajah Mada curriculum emphasizes themes that are often debated and cause differences in religious practice within society, so that students who take this course will develop tolerant, moderate attitudes and compassion for all. Meanwhile, The Islamic Religious Education as compulsory subject at Universitas Syiah Kuala places greater emphasis on the fundamentals of Islam and strengthening the character of true muslims by understanding the challenges faced by the muslim community and countering deviant ideologies. Second, the strategies employed by UGM and USK to prevent the infiltration of radicalism among students through the strengthening of Islamic Religious Education emphasize: (1) a counter-narrative approach to extremism, public lectures featuring former terrorists, teaching assistance and monitoring, in-depth discussions with a multi-perspective approach, instilling tolerance, and promoting religious moderation. Research implications/limitations – The implication of this study is the importance of Islamis Religious Education learning in higher education that emphasizes the values of tolerance, moderation, and strengthening of multi-perspective religious insights as well as the experiences of radical actors Originality/value – The findings of this study contribute to strengthening Islamic education in higher education as a strategy to counter radicalism among students.